LEVEL OF PATIENTS’ SATISFACTION FROM PHYSICAL THERAPY SERVICES IN OUTPATIENT DEPARTMENT OF TERTIARY CARE HOSPITALS IN PESHAWAR: A CROSS-SECTIONAL SURVEY - Asad Khan; Sakeena Masoud; Muhammad Yasir; Syed Alamdar Hussain; Usman Farooq; Huma Balqias; Syeda Kaniz Fatima Haider (The Rehabilitation Journal, 2022)
Background: Patient satisfaction is a reference point of that degree to which a client is satisfied with the attention and treatment or health care services they get from their health care professional. It provides an idea about the intervention that is effective or not and removes the different malpractice claims. Objective: To determine the level of patients’ satisfaction in outpatient departments of physiotherapy in tertiary care hospitals of Peshawar. Methodology: This study was a cross sectional survey in which purposive sampling was used and data was collected through MED-RISK patient satisfaction questionnaire. Both male and female aged between 18 to 75 and had received at least 3 or more sessions of physiotherapy were recruited in the study The sample size was n=375, participants were selected from physiotherapy (OPD) of Tertiary Care Hospitals of Peshawar. The 13 items, slightly modified form of Med Risk Patient Satisfaction instrument (MRPS) was used for data collection. The data was analyzed and presented in the form of frequencies and percentages. Results: The respondent characteristics of 375 patient showed that more than half were male 245 (65.3%) and the remaining were female 130 (34.7%). The overall patient satisfaction from physical therapy services was 4.38±0.70 which showed that majority of the participants were satisfied with physical therapy services. When comparing the public and private setups, it was observed that participant received PT services in private setup are significantly satisfied (p<0.05) with services as compared to public setups.  Conclusion: The level of patient’s satisfaction receiving physiotherapy health services in tertiary care hospitals of Peshawar can be considered high. Lower back pain was the most presenting symptom for the selected population receiving physiotherapy treatment. The patient education showed the highest mean as compared to other factors. The private sector showed statistically high level of satisfaction as compared to the public sector while practically the services being delivered by private and public sector were on same level. Keywords: Med- Risk, Outpatient Department, Patient satisfaction, Physical Therapy, Tertiary care hospitals